"All lives matter": How districts co-opt equity language and maintain the status quo - Tiffanie Lewis-Durham (Arizona State University, 2020)
The term "equity" is widely used by educational policy makers to describe myriad programs and practices aimed at closing the supposed racial achievement gap. Research about the way equity has been used in these policies typically explores how policy actors with low will and capacity frame and implement their reforms. Few studies, however, explore equity-oriented reforms initiated and supported by policy makers who claim to fervently support educational equity. The purpose of this critical policy analysis was to examine how the rhetoric used by equity-supportive policy actors may have reinforced neoliberal ideas and inadvertently maintained white innocence and color-blind racism. Examining the Community Schools policy in New York City schools, this study found that some equity initiatives are circumscribed by their focus on "all lives", which can unwittingly reinforce the status quo in schools.